2020
DOI: 10.1088/2632-959x/ab8481
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-mediated dispersions of carbon nano-onions in aqueous solution

Abstract: In this work, we investigate the ability of different surfactants to form homogeneous and stable dispersions of carbon nano-onions (CNOs) in water via non-covalent interactions. For our purposes, we select three ionic surfactants, namely the cationic hexadecyltrimethylammonium bromide (CTAB) and the two anionic deoxycholic acid sodium salt (DCAS) and sodium dodecylbenzenesulfonate (SDBS). We examine the dispersing efficacy at dispersing CNOs and long-term stability by UV-vis absorption spectroscopy, dynamic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Covalent strategies have the advantage to introduce onto the CNM surface polar groups such as carboxylic acid groups, leading to a water soluble and stable derivatives [ 41 ]. However, this strategy leads to the disruption of the regular sp 2 -hybridized network, thus potentially affecting the intrinsic properties of the materials [ 42 , 43 ]. Therefore, in order to preserve the pristine surface of CNMs and thus their native physicochemical properties, non-covalent approaches are typically preferred [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Covalent strategies have the advantage to introduce onto the CNM surface polar groups such as carboxylic acid groups, leading to a water soluble and stable derivatives [ 41 ]. However, this strategy leads to the disruption of the regular sp 2 -hybridized network, thus potentially affecting the intrinsic properties of the materials [ 42 , 43 ]. Therefore, in order to preserve the pristine surface of CNMs and thus their native physicochemical properties, non-covalent approaches are typically preferred [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other CNMs, pristine CNOs are highly hydrophobic and tend not to disperse well in organic and aqueous solvents due to aggregation, which can limit practical applications [ 24 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…These dispersions were mainly used as a comparison to cellulose-based dispersions, which were found to be more effective. ACSs are capable of dispersing CNOs, as demonstrated by our group using hexadecyltrimethylammonium bromide (CTAB) and SDBS [48] (Table 4 (1)). This study also found that ACSs with negatively charged head groups are more effective at dispersing CNOs than their cationic counterparts.…”
Section: Alkyl Chain Surfactantsmentioning
confidence: 97%
“…The aqueous dispersion was found to be stable for six weeks, with a CNO: SDC mass ratio of 2:1 found to be ideal for surfactant efficiency. This CNO functionalisation was driven by hydrophobic interactions [48].…”
Section: Bile Acid Saltsmentioning
confidence: 99%
See 1 more Smart Citation